Studi Perbandingan Antara Indonesia dengan Berbagai Negara di Dunia - Yuswardi, Yuswardi; Fahlevi, Renza; Marninda, Caroline; Angela, Angela; Wijaya, Charlie; Martinus, Titan; Bhuan, Sun (JURNAL ADMINISTRASI KANTOR; Vol 11 No 1 (2023): Jurnal Administrasi Kantor (Juni 2023), 2023)
Indonesia is the fourth largest country in the world, and a country can be said to consist of human, political, economic and cultural resources. To find out these 4 aspects, a comparative analysis of the economic, political, cultural and human resources aspects of Indonesia and other countries is carried out.  which is the aim of the research. The results of the study show that Indonesia is facing unemployment problems due to the low quality of human resources.  Indonesia as an agricultural country has good export value, although it has not been able to compete with Thailand and Vietnam.  However, Indonesia is included in an emerging market making it possible to follow global competition.  In order to create a new global environment and increase employment opportunities, Indonesia can reduce the export trade of raw goods and accept foreign investment.  However, Indonesia has a high collectivity which is reflected in the solidarity and thickness of customs in the world of work such as the existence of a power gap, gender inequality, with high context business communication.  As for suggestions, in an effort to reduce the number of unemployed, the state can increase human resources by paying attention to the quality of education.  Adjustment to the work environment is also required, as well as leaving bad habits at work and prioritizing professionalism and punctuality.  Infrastructure development is also needed to simplify and reduce the cost of export and import logistics activities.  Then the ease of licensing the business sector for PMA can make it easier for business people to tie up capital. Keywords : Economic, Culture, Politic, Human Resource